2015
DOI: 10.4314/ijbcs.v9i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Tomato pomace powder ameliorated cisplatin-induced microanatomical alterations in brain of Wistar rats

Abstract: Cisplatin chemotherapy is associated with neurotoxicity. Oxidative stress has been associated with its pathogenesis. Tomato (Lycopersicon esculentum) pomace powder (TPP) may be a preventive agent by virtue of its known antioxidant property. The possible protective role of TPP against cisplatin-induced alteration of the microanatomy of rat brain was investigated. Thirty rats were divided equally into five groups: control, propylene glycol, TPP, cisplatin (10 mg/kg i.p.); TPP 50 mg/kg plus cisplatin (10 mg/kg i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Histological examination of hippocampus sections in group II (MSG) showed degenerative changes in the pyramidal and granule cells of CA1, CA3 and dentate gyrus however some cells appeared with pale-staining nuclei. Similar findings were reported by Owoeye and Onwuka, 2015 [21] .…”
Section: Discussionsupporting
confidence: 92%
“…Histological examination of hippocampus sections in group II (MSG) showed degenerative changes in the pyramidal and granule cells of CA1, CA3 and dentate gyrus however some cells appeared with pale-staining nuclei. Similar findings were reported by Owoeye and Onwuka, 2015 [21] .…”
Section: Discussionsupporting
confidence: 92%
“…Histological study of brain sections of thalidomide and carboplatin-treated group showed loss of normal structure, neuronal degeneration with pyknotic nuclei, and dilation of blood capillary with hemorrhage. Similarly, cisplatin has negative effects on cerebellar cortex neurons [ 51 ]. Gulec et al [ 52 ] suggested that sufficient levels of cisplatin have been shown to cause toxicity in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…• Group I (cisplatin treated group): rats were injected with 10 mg/kg of cisplatin IP on the 6 th and the 13th days of the study [9] .…”
Section: Experimental Groupsmentioning
confidence: 99%